(3eNJUQ Sc GdOQjf aj Md GdfjQjf hGSJNQGL GdCgdIs - (3jMji Hf eMeO Hf eMeO GdQYjfi GdNWGH (B( (3GdNWGH (B) (3Gdecj GdeGdcjs; (3CMeO Hf ehSi Hf YHO GdZaGQs
(3ChdgG (B:s
(3jbhd jMji Hf eMeO GdNWGH GdMeO ddg GdPi LYd ai GdSeGA HQhLkG CeG HYO agPg QSGdI dWjaI ai eYQaI GdTeS hGdbeQ hGdLhRgQ dYGe cGed s
(3BNQgG (B:s
(3hGdbeQ ai GdYbQH aYedJ Pdc hHbjJ CNJe heG ChOYg Gddg JYGdi ef GdCSQGQ ai gPG GdYGde hgPG BNQ eG jSQ Gddg GdcQje LeYg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3ai GdeYgO fSNI ef Sdc GdOQfji ai Md GdfjQHf HQbe (B126 (3adcs
(3HgG LOGhds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdadcs